2004
DOI: 10.1016/j.molcel.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the KU80 Pathway on NHEJ-Induced Genome Rearrangements in Mammalian Cells

Abstract: Using a substrate measuring deletion or inversion of an I-SceI-excised fragment and both accurate and inaccurate rejoining, we determined the impact of non-homologous end-joining (NHEJ) on mammalian chromosome rearrangements. Deletion is 2- to 8-fold more efficient than inversion, independent of the DNA ends structure. KU80 controls accurate rejoining, whereas in absence of KU mutagenic rejoining, particularly microhomology-mediated repair, occurs efficiently. In cells bearing both the NHEJ and a homologous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
328
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(361 citation statements)
references
References 30 publications
32
328
0
Order By: Relevance
“…Among the different rearrangements, deletions are two-to eightfold more frequent than inversion. This may be due in part to the fact that deletion and inversion require one and two ligation events, respectively (Guirouilh-Barbat et al, 2004). Our results demonstrated that only full-length Vpr affects Ku endogenous levels and disturbs Ku's protective role by preventing NHEJ.…”
Section: Discussionmentioning
confidence: 70%
“…Among the different rearrangements, deletions are two-to eightfold more frequent than inversion. This may be due in part to the fact that deletion and inversion require one and two ligation events, respectively (Guirouilh-Barbat et al, 2004). Our results demonstrated that only full-length Vpr affects Ku endogenous levels and disturbs Ku's protective role by preventing NHEJ.…”
Section: Discussionmentioning
confidence: 70%
“…To this end, we utilized cell lines that contain stably integrated reporters to assess the rates of HR (DR-GFP 10,11 ) and NHEJ. 12 --14 For NHEJ, we used cell lines containing two types of NHEJ-reporter substrates; the pCOH-CD4 that permits analysis of the NHEJ of two distal ends (separated by 3.2 kb), 12,13 and a GFP-based substrate, 14 to measure the NHEJ on closely adjacent ends, separated by only 34 bp. 14 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, silencing of classical NHEJ factors that affect the efficiency of end ligation affect the fidelity of repair as well. 13 An alternative scenario could be that NUP153 negatively regulates a protein that promotes HR. Furthermore, we can imagine that the nuclear soluble fraction of 53BP1 has a role in the regulation of the repair pathways, by sequestering certain factors away from the break.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in HR or in NHEJ can lead to genome instability and tumorigenesis (Liu et al, 1998;Sonoda et al, 1998;Difilippantonio et al, 2000;Ferguson et al, 2000a;Bertrand et al, 2003). However, both functional HR and NHEJ can be responsible for genome rearrangements: (i) functional HR between repeated sequences dispersed through the genome can also lead to genome rearrangements (Purandare and Patel, 1997;Richardson and Jasin, 2000b;Bertrand et al, 2004), and (ii) functional Ku autoantigen protein (KU)-dependent as well as KU-independent NHEJ can generate genetic rearrangements (Guirouilh-Barbat et al, 2004). This shows the importance of a precise DSB repair regulation in mammalian cells for the equilibrium between genetic stability and diversity.…”
Section: Introductionmentioning
confidence: 99%